Understanding London Dispersion Forces in Solution - Quantification of Noncovalent Interactions with a Bifluorenylidene Molecular Balance - Wilming, Finn; Justus Liebig University Giessen (My University, 2023)
London dispersion interactions received little attention in the first decades after their discovery because of the misconception that they are generally weak and, could accordingly only have negligible influence on chemical processes. Today it is known that, although the stabilization between two individual atoms caused by London dispersion is indeed rather weak, these small stabilizing contributions can quickly accumulate to a significant force in larger systems. London dispersion interactions can therefore strongly influence the structure and stability of molecules and the selectivity of chemical reactions. In this work, a better understanding of London dispersion interactions in solution was obtained using a molecular balance. These are small molecular devices that can be used to measure noncovalent interactions at the microscopic scale. This is of particular importance because over the past several years there has been a debate about the extent to which stabilization caused by London dispersion in solution is attenuated by competitive interactions with the solvent. In the first publication, we present the synthesis and various solvent dependent NMR measurements of a hydrocarbon molecular balance based on the 9,9'-bifluorenylidene backbone. Since the different E/Z-ratios of this molecular balance in a group of 15 organic solvents are mainly induced by the solvophobic effect, it allows us to understand the influence that the choice of solvent can have on the strength of solvophobic effects. These effects are particularly important to fully understand opportunities and limits of the strategic use of London dispersion interactions in solution, where both forces oftentimes occur simultaneously. In the second publication, we synthesized a total of 14 differently substituted molecular balances based on the same nonpolar backbone. We studied their E/Z-equilibrium by NMR in seven different organic solvents. The Z-isomer was favored in almost all experiments. We used computations to show that the Z-isomers higher stability is caused by London dispersion interactions between the neighboring substituents and therefore underlined that London dispersion interactions in solution are not fully compensated by competing interactions with the solvent.
Keywords: London Dispersion; Nichtkovalente Wechselwirkungen; Molekulare Waagen; Physikalisch Organische Chemie; ddc:540